STUDY OF THE FEATURES OF ACADEMIC PROCRASTINATION OF YOUTH STUDENTS - Subashkevych, Iryna (Socio-economic relations in the digital society, 2023)
This article delves into the concept of academic procrastination as a psychological phenomenon that serves as a significant barrier to personal development and lies at the core of the issue of an individual’s incapacity to shape a cohesive life vision. This vision encompasses both short-term and long-term planning, goal-setting, and behavior geared toward self-realization. Various approaches to comprehending the essence of this phenomenon, including psychodynamic, behavioral, and cognitive perspectives, are examined. The study reveals that academic procrastination is a considerable issue among student youth, with 75% exhibiting a high level of academic procrastination. Among students in the 3rd and 4th years, a greater inclination towards elevated levels of academic procrastination is observed, whereas 1st and 2nd-year students display higher motivation and less inclination towards procrastination. This could be associated with shifts in study habits and increased workload upon transitioning to higher years. Students in the 3rd and 4th years necessitate the development of time management strategies and overcoming procrastination to attain success. The primary cause of academic procrastination among student youth, according to survey results, is academic perfectionism (76%), while a lack of academic motivation and anxiety are identified as less provocative factors. Approximately half of the respondents are found to be internals, the majority of whom possess a moderate level of internal stimuli orientation. In contrast, 55% of the respondents are classified as externals, relying more on external factors in their academic pursuits.